D-dimers are associated with coronary artery disease severity assessed using Syntax and Syntax II scores in patients with ST elevation myocardial infarction - Caner Türkoğlu; Hazar Harbalıoğlu; Taner Şeker; Ahmet Oytun Baykan; Onur Kadir Uysal (Revista Portuguesa de Cardiologia, 2020)
Introduction and objectives: D-dimers are a determinant of hypercoagulable state and have been found to be related to acute coronary syndromes. We aimed to establish the association between increased D-dimer levels and coronary artery disease (CAD) severity using SYNTAX Score (SS) II in patients with ST elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention (PCI). Methods: This retrospective study included 300 consecutive patients (81.7% males, mean age 55±12 years) with STEMI who underwent a primary PCI. Patients were divided into two groups according to their median SSII [SSII<25 as a low group (n=151) and SSII≥25 as a high group (n=149)]. Blood samples for D-dimers and the other biochemical parameters were obtained from each patient at admission. Results: When compared with the low SSII group, frequency of female gender, no-reflow phenomenon, D-dimer levels, thrombus score, creatine kinase MB and troponin were significantly higher, whereas left ventricular ejection fraction (LVEF) and glomerular filtration rate (GFR) were lower in the high SSII group (p<0.05, for all). D-dimer levels, thrombus score, LVEF, GFR and no-reflow phenomenon were independent predictors of CAD severity (p<0.05, for all). Receiver operating characteristic curve analysis showed that the D-dimer cut-off value for predicting the severity of CAD was 0.26 μg/ml (69.8% sensitivity and 65.6% specificity, p<0.001). Conclusion: Increased D-dimer levels are associated with the severity of CAD based on Syntax Score II, in patients with STEMI who successfully underwent revascularization with a primary PCI. Resumo: Introdução e objetivos: Os D-dímeros elevados refletem um estado de hipercoagulabilidade determinante que se relaciona com as síndromes coronárias agudas (SCA). Foi nosso objetivo determinar a associação entre os níveis elevados de D-dímeros e a gravidade da doença coronária utilizando o score SYNTAX (SS) em doentes com enfarte do miocárdio com elevação do segmento ST (STEMI) submetidos a intervenção coronária percutânea (ICP). Métodos: Este estudo retrospetivo incluiu 300 doentes consecutivos (homens – 81,7% com média de 55±12 anos) com STEMI submetidos a ICP. Os doentes foram divididos em dois grupos de acordo com o SSII médio [SSII<25 no grupo de baixo risco (n=151) e SSII≥25 no grupo de alto risco (n=149)]. As análises de sangue para avaliação dos D-dímeros e de outros parâmetros bioquímicos foram efetuadas durante a admissão hospitalar em todos os doentes. Resultados: No grupo SSII de alto risco, o género feminino, o «fenómeno no-reflow», os níveis dos D-dímeros, o score de trombos, a creatinaquinase MB (CK-MB) e a troponina foram significativamente superiores aos grupos SSII de baixo risco (p<0,05); a fração de ejeção ventricular esquerda (FEVE) e a taxa de filtração glomerular (TFG) foram inferiores (p<0,05) aos do grupo de baixo risco de SSII. Os níveis dos D-dímeros, o score de trombos, a FEVE, a TFG o fenómeno no-reflow foram fatores predizentes independentes da gravidade da doença coronária (p<0,05 em todos). A análise da curva ROC (receiver operating characteristic curve) demonstrou que o valor cut-off dos D-dímeros para prognóstico da gravidade doença coronária foi de 0,26 μg/ml (sensibilidade 69,8% e especificidade 65,6%, p<0,001). Conclusão: O nível D-dímeros está associado à gravidade da doença coronária avaliada pelo Score Syntax II em doentes com STEMI, bem-sucedidos na revascularização com ICP.